2021
DOI: 10.1021/acs.chemrestox.0c00274
|View full text |Cite
|
Sign up to set email alerts
|

Integrated QSAR and Adverse Outcome Pathway Analysis of Chemicals Released on 3D Printing Using Acrylonitrile Butadiene Styrene

Abstract: Additive manufacturing commonly known as 3D printing has numerous applications in several domains including material and biomedical technologies and has emerged as a tool of capabilities by providing fast, highly customized, and cost-effective solutions. However, the impact of the printing materials and chemicals present in the printing fumes has raised concerns about their adverse potential affecting humans and the environment. Thus, it is necessary to understand the properties of the chemicals emitted during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 52 publications
0
3
0
1
Order By: Relevance
“…Pandit i wsp. [31] wykazali, że stosowanie filamentów ABS w produkcji przyrostowej może prowadzić do toksyczności inhalacyjnej i po podaniu doustnym. Ujawniono, że większość substancji chemicznych emitowanych podczas druku 3D cechowała się wysokim poziomem wchłaniania w jelitach i potencjałem przenikania przez barierę krew-mózg.…”
Section: Toksyczność Materiałów Wykorzystywanych W Technologii Fdmunclassified
“…Pandit i wsp. [31] wykazali, że stosowanie filamentów ABS w produkcji przyrostowej może prowadzić do toksyczności inhalacyjnej i po podaniu doustnym. Ujawniono, że większość substancji chemicznych emitowanych podczas druku 3D cechowała się wysokim poziomem wchłaniania w jelitach i potencjałem przenikania przez barierę krew-mózg.…”
Section: Toksyczność Materiałów Wykorzystywanych W Technologii Fdmunclassified
“…Furthermore, there is increased awareness of potentially harmful airborne particles and VOCs emitted during the process of 3D printing (Floyd et al, 2017;Wojtyła et al, 2020), with ABS, in particular, shown to present potential health risks without suitable ventilation (Pandit et al, 2021, Farcas et al, 2019. Higher-end industrial 3D printers and processes also present airborne particle hazards if not adequately ventilated (Kangas et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…, 2017; Wojtyła et al. , 2020), with ABS, in particular, shown to present potential health risks without suitable ventilation (Pandit et al. , 2021, Farcas et al.…”
Section: Introductionmentioning
confidence: 99%
“…Any comprehensive analysis requires a database of well-curated data. The ChEMBL database contains different bioactivity data types from early discovery to postclinical data on marketed drugs and was used in multiple prior toxicity studies, including at least four articles included here. ,,, In this issue, Hunter et al extended the ChEMBL safety-related information for approved drugs to include the assignment of toxicity based on their withdrawn status and/or black box warning information described on medicinal product labels. These data can become an additional important asset for future toxicity prediction studies.…”
mentioning
confidence: 99%